Landscape patterns and their spatial associations with ecosystem service balance: Insights from a rapidly urbanizing coastal region of southeastern China - Chen, Weilian; Jiang, Chong; Wang, Yixin; Liu, Xiaoding; Dong, Binbin; Yang, Ji; Huang, Wumeng (Frontiers in Environmental Science, 2022)
Assessing ecosystem service (ES) balance and exploring critical drivers are crucial for landscape management. However, a lack of understanding of the determinants of the ES supply–demand budget, their spillover effects, and spatial variabilities offsets the efficacy of landscape planning and ecosystem conservation. This novel study attempted to close this gap by quantifying ES budget using an expert knowledge-based supply–demand matrix and explored its dependencies through spatial econometrics and geographically weighted regression approaches instead of using ordinary model simulation and conventional statistical analysis. The overall patterns of ES balance in the southeastern coast were found to have remained stable in 1980, 2000, and 2017, although remarkable ES deficits were identified in hotspots of rapid urbanization. The ES balance was negatively associated with the proportions of built-up land and cropland (p < 0.0001) and exhibited positive associations with the proportions of woodland and grassland (p < 0.0001). Landscape structure and population density were identified as the primary determinants of ES balance and exhibited spatial variability and spillover effects (i.e., determining ES balance in both individual and adjacent units). These findings demonstrate the significance of spatial disparities and external effects of determinants of the supply–demand budget in integrative landscape governance. Consequently, localized and targeted strategies for landscape planning are increasingly needed to optimize landscape configuration and alleviate ES imbalance according to individual socioeconomic conditions and landscape structures. In addition, the spillover effects demonstrate that the maintenance of regional ES balance and ecosystem sustainability depends not only on individual areas but also on cross-regional collaborations with neighboring regions. These findings have critical implications on strategy formulation for coastal landscape management and ecosystem sustainability.